1999
DOI: 10.1176/ajp.156.10.1580
|View full text |Cite
|
Sign up to set email alerts
|

Lamina-Specific Alterations in the Dopamine Innervation of the Prefrontal Cortex in Schizophrenic Subjects

Abstract: These findings reveal that schizophrenia is associated with an altered dopamine innervation of prefrontal cortex area 9 that is lamina- and neurotransmitter-specific and that does not appear to be a consequence of pharmacological treatment. Together, these data provide direct evidence for a disturbance in dopamine neurotransmission in the prefrontal cortex of schizophrenic subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
200
1
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 320 publications
(217 citation statements)
references
References 57 publications
14
200
1
2
Order By: Relevance
“…The laminar imbalance of COMT expression, which presumably leads to imbalance of dopamine availability at the synaptic level, may contribute to dysregulation of pyramidal neuronal circuitry in the prefrontal cortex, albeit to a relatively small degree. In an earlier immunohistochemical study of dopamine terminals in the dorsomedial prefrontal cortex, patients with schizophrenia displayed significantly reduced dopaminergic innervation in the deeper layers (Akil et al, 1999). The reduction of dopaminergic input in deep layers has also been observed in the dorsolateral region (Akil M, personal communication).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The laminar imbalance of COMT expression, which presumably leads to imbalance of dopamine availability at the synaptic level, may contribute to dysregulation of pyramidal neuronal circuitry in the prefrontal cortex, albeit to a relatively small degree. In an earlier immunohistochemical study of dopamine terminals in the dorsomedial prefrontal cortex, patients with schizophrenia displayed significantly reduced dopaminergic innervation in the deeper layers (Akil et al, 1999). The reduction of dopaminergic input in deep layers has also been observed in the dorsolateral region (Akil M, personal communication).…”
Section: Discussionmentioning
confidence: 91%
“…Previous anatomical studies in monkey (Goldman-Rakic et al, 1989;Krimer et al, 1997;Lewis, 1992;Smiley and Goldman-Rakic, 1993) and human (Akil et al, 1999;Lewis, 1992) brain have demonstrated that dopaminergic projections to DLPFC are highly organized and distributed in a bilaminar manner at high densities in the superficial (I/II) and deep layers (V/VI), whereas the distribution is more uniform in the dorsomedial region of this cortical area. The majority of dopaminergic terminals synapse on pyramidal neurons, while dopaminergic contacts on nonpyramidal neurons are much less dense and are irregularly distributed (Goldman-Rakic et al, 1989;Krimer et al, 1997;Smiley and Goldman-Rakic, 1993).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Post‐mortem tissue analysis from the former has previously indicated reduced prefrontal dopaminergic innervation (Akil et al, 1999). Furthermore, aged subjects with working memory deficits showed reduced prefrontal dopaminergic neurotransmitter tonus (Ota et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…These findings indicate that the D 1 receptor has an important role in modulating cognitive performance under the control of the PFC and are consistent with human data showing beneficial effects of the mixed D 1 /D 2 receptor agonist, http://www.guidetopharmacology.org/GRAC/LigandDisplayForward?ligandId=48 (on longer, but not shorter, delays), in a delay‐dependent spatial working paradigm in humans (Muller et al, 1998). Post‐mortem tissue analysis of patients with schizophrenia indicates they have reduced dopaminergic innervation of the PFC (Akil et al ., 1999), suggesting that an altered dopaminergic state in this brain area could be an important pathophysiological aspect of the disease and may contribute to the cognitive disturbances seen in this patient population. PET studies demonstrate increased D 1 receptor availability in the PFC of drug‐naïve patients with schizophrenia, as well as patients with schizotypal personality disorder and those with schizophrenia and a medication history.…”
Section: Introductionmentioning
confidence: 99%